SOBO: A Feedback Bot to Nudge Code Quality in Programming Courses - Bobadilla, Sofia; Glassey, Richard; Bergel, Alexandre; Monperrus, Martin (IEEE software, 2024)
This paper presents SOBO, a bot we designed to automatically provide feedback on code quality to undergraduate students. SOBO has been deployed in a course at the KTH Royal Institute of Technology in Sweden with more than 130 students.